Ribonucleotide incorporation into mitochondrial DNA drives inflammation - Amir Bahat; Dusanka Milenkovic; Eileen Cors; Mabel Barnett; Sadig Niftullayev; Athanasios Katsalifis; Marc Schwill; Petra Kirschner; Thomas MacVicar; Patrick Giavalisco; Louise Jenninger; Anders R. Clausen; et al. (Nature, 2025)
Abstract Metabolic dysregulation can lead to inflammatory responses 1,2 . Imbalanced nucleotide synthesis triggers the release of mitochondrial DNA (mtDNA) to the cytosol and an innate immune response through cGAS–STING signalling 3 . However, how nucleotide deficiency drives mtDNA-dependent inflammation has not been elucidated. Here we show that nucleotide imbalance leads to an increased misincorporation of ribonucleotides into mtDNA during age-dependent renal inflammation in a mouse model lacking the mitochondrial exonuclease MGME1 4 , in various tissues of aged mice and in cells lacking the mitochondrial i-AAA protease YME1L. Similarly, reduced deoxyribonucleotide synthesis increases the ribonucleotide content of mtDNA in cell-cycle-arrested senescent cells. This leads to mtDNA release into the cytosol, cGAS–STING activation and the mtDNA-dependent senescence-associated secretory phenotype (SASP), which can be suppressed by exogenously added deoxyribonucleosides. Our results highlight the sensitivity of mtDNA to aberrant ribonucleotide incorporation and show that imbalanced nucleotide metabolism leads to age- and mtDNA-dependent inflammatory responses and SASP in senescence.